Silver Nanocoral Structures on Electrodes. A Suitable Platform for Protein-Based Bioelectronic Devices. - Feng, Jiu-Ju (2008)
We report a simple strategy for constructing silver coral-like nanostructures on graphite electrodes suitable for bioelectronic applications. The nanocorals are conductive, have dimensions adequate for high protein loading, and are remarkably stable. They also provide a strong Raman surface enhancement that allows for in situ structural characterization of the immobilized proteins. The potential of the Ag nanocoral electrodes is exemplified by the construction and characterization of a hydrogen peroxide amperometric sensor based on cytochrome c.